ANALISIS PENGARUH INTENSITAS CAHAYA TERHADAP DAYA YANG DIHASILKAN PADA PANEL SURYA 600 Wp - Hamzah, R.A. Nur'aini; Annisah, Masayu; Lutfi, Iskandar (Teknik Elektro Polsri, 2024)
This research looks at how light intensity affects the power generated by a 640 WP solar panel. Given the reduction in fossil energy production and the global commitment to reduce greenhouse gas emissions, the use of renewable energy has increased. Indonesia has a great opportunity for solar power development as it has a solar energy potential of about 4.5 kilowatt hours per day. This study was conducted at KWT Kemuning Farm from March to July 2024. The measurement results show that there is a significant correlation between light intensity and power generated. The results show that the light intensity is directly proportional to the power generated. The highest light intensity of 156300 Lux at 13:00 WIB produced 127.08 Watts of power, while the lowest light intensity of 26300 Lux at 16:00 WIB only produced 10.01 Watts of power. Power fluctuations were seen throughout the day, with the highest average power peak occurring between 11:00 am and 2:00 pm. This study provides important information on the relationship between light intensity and power generated, which can be used to improve the efficiency of solar panel technology in the future.